Preliminary results of the geoarchaeological survey conducted before the archaeological excavation at Belvárdgyula. Reconstruction of landscape evolution in the floodplain of Karasica - Balogh, Réka; Dezső, József; Kovaliczky, Gergely (JOURNAL OF LANDSCAPE ECOLOGY, 2012)
In the loess area of Baranya Hills, Southeast from Belvárdgyula (Baranya County), there is a five meter tall island-like natural formation in the floodplain at the confluence of the Karasica and the Vasas-Belvárdi water course. Archaeological excavations in the surrounding environment were sporadic in the past. The research of this formation started in October 2010. For answering the revealed questions, we have used pedological, morphological and geoarchaeological methods. Soil samples recovered with the drillings were subjected to mechanical analysis, carbonate and mould content determination, as well as the identification of phosphorus and potassium content. These two elements were used tot indicate human activity. To better understand pedological processes we prepared thin sections from important layers, and performed micromorphological analysis to specify the reconstruction of landscape evolution. By using these results we have framed the possible process of the hill’s evolution. The floodplain itself is morphologically divided into two, well-recognizable parts: one is younger and lower, the second one is older and higher floodplain. The difference between them is only one meter. The island-like hill lies between them, which actually divides the floodplain. A cross-section of the formation was compiled based upon 24 drillings. Three different soil typeswere identified: chernozem meadow, meadow (typical) and intermediate soil type. Since the beginning of the Holocene the exfoliating floodplain of Karasica has been filled up with reddish-brown and brown silty and sandy texture granite-based material, which originates from the Southern Mecsek mountains and is naturally mixed with accumulated sediments. During the period of the Late Neolithic, the anthropogenic land use became more intensive; the agricultural areas have grown, therefore the deforestations reached a higher level. This processes facilitate the surface fluvial erosion from the direction of the Western and Northwestern loess hills. Presumably, in this period the Vasas-Belvárdi River activated and formed a higher shape of its present-day elevation. Meanwhile, and after the processes, the floodplain of Karacisa sank again and evolved a younger and lower floodplain. The aim of our research was to determine natural and anthropogenic effects in the hill’s evolution. Based on these results we are able to provide information for archaeologist regarding the importance of a future exca- vation. The examination detected the traces of human activity, On the score of all results, presumably the hill formed by natural evolution with anthropogenic impacts.